Investigation of Risk and Protective Factors in Women Attempting Suicide: A Phenomenological Approach - Sepideh Kiyanzad; Hamid Taher Neshat Doost; Hosseinali Mehrabi; Sayyed Ghafoor Mousavi (پژوهش‌های کاربردی روانشناختی, 2022)
The aim of this study was to investigate the lived experiences of women attempting suicide regarding risk factors and protective factors. The study method was qualitative and the phenomenological approach. Sampling was purposeful and after semi-structured interviews with 15 women who attempted suicide, saturation was achieved. Seven-step Colaizzi method was used for analysis. The reliability of the findings was confirmed based on Lincoln and Guba criteria. Identified four themes and eight subthemes for risk factors: Tensions in family relationships (subthemes: Argument and conflict, emotional indifference, Lack of marital loyalty), Failed relationships (self-blame, loss), Mental suffering (Living in sorrow and despair, Sense of being a burden, Perception of inefficiency) and theme of poverty and unemployment. Four themes were also extracted regarding protective factors: emotional attachment to a family member, sense of responsibility towards children, religious beliefs, and perceived social support. The results of this study indicate the importance of family and emotional relationships as well as untreated depression as the main factors identified as effective. Outcomes and key implications of this study were mainly related to improving the treatment experiences of women surviving suicide and other high-risk populations through the development of preventive interventions commensurate with the findings.